Pengaruh Harga, Persediaan Barang dan Citra Merek Terhadap Keputusan Pembelian Konsumen Melalui Minat Beli Sebagai variabel Intervening - Uswatun Hasanah; Moch. Chotib; Hersa Farida Qoriani (Jurnal Syntax Admiration, 2023)
Consumers buy goods or services to fulfill their needs. In the process of fulfilling these needs, consumers employ various methods. One of them is seeking information related to the product they intend to purchase, such as its price and availability in the store they plan to visit. This is because the majority of consumers opt for affordable items with comparable quality, thus saving time and effort. This research adopts a qualitative approach, focusing on hypothesis testing with measurable data to draw conclusions that can be generalized. The population in this study is infinite, encompassing all consumers of the BASMALAH store in Jember Regency. The sampling method used is incidental sampling, which selects samples based on chance. The representative sample size for the study is 21 x 5 = 105 respondents. Data analysis is conducted using path analysis, developed from regression analysis, and hypothesis testing is assisted by SPSS version 23. The analysis results indicate that the price variable has a significant influence on consumer buying interest, with a standardized coefficient of 0.219. The inventory variable also significantly affects consumer buying interest, with a standardized coefficient of 0.346. The brand image variable has an effect, but it is not significant in influencing consumer buying interest, with a standardized coefficient of 0.158. The price variable significantly influences consumer purchase decisions, with a standardized coefficient of 0.384. The inventory variable has an effect, but it is not significant in influencing purchase decisions, with a standardized coefficient of 0.207. Brand image has an effect, but it is not significant in influencing consumer purchase decisions, with a standardized coefficient of 0.188. The price variable significantly influences purchase decisions through buying interest. The inventory variable has an effect, but it is not significant in influencing purchase decisions through buying interest.